Motor and Non-motor Features: Differences between Patients with Isolated Essential Tremor and Patients with Both Essential Tremor and Parkinson's Disease - Apostolia Ghika; Andreas Kyrozis; Constantinos Potagas; Elan D. Louis (Tremor and Other Hyperkinetic Movements, 2015)
Background: Patients with essential tremor (ET) who develop Parkinson’s disease (ET->PD) may differ with respect to motor features (MFs) and non-motor features (NMFs) from patients with isolated ET. Few studies have assessed this issue. Methods: In this retrospective chart review, we analyzed data on MFs and NMFs of 175 patients, including 54 ET->PD and 121 ET, actively followed in the Athens University 1st Neurology Department. Results: Significantly more ET->PD than ET patients reported asymmetric tremor at ET onset (68.5% vs. 14.9%, p<0.001).  Significantly more ET than ET->PD patients had head tremor (43.5% vs. 13.2%, p<0.001) and cerebellar signs (41.3% vs. 9.3%, p<0.001). More ET than ET->PD patients reported hearing impairment (65.3% vs. 28.3%, p<0.001) and restless legs syndrome (34.8% vs. 3.7%, p<0.001). Conversely, a larger proportion of ET->PD than ET patients reported rapid eye movement behavior disorder (51.9% vs. 10.0%, p<0.001), constipation (67.9% vs. 36.4%, p<0.001), and olfactory dysfunction (83.3% vs. 36.4%, p<0.001). Discussion: The subset of ET->PD patients may have distinct MFs and NMFs that should be assessed further for the possible predictive value for the emergence of PD.